Dampak Citra Merek dan Harga terhadap Kepuasan Konsumen (Study Kasus Keisya Laudry di Kota Jambi) - Evi Fauzani; Machfia Win Hidayati (Universitas Batanghari Jambi, 2022)
This study aims to purpose and analyze the impect of brand image and price on costumer satisfaction (case study of Keisya Laundry in Jambi City). This type of research used is descriptive quantitative .Researchers use SPSS 16 to test the research . The sample used in this study is the result of a questionnaire totaling 100 consumer of Keisya Laundry as primary data and secondary data obtained from documentation and filling out a questionnaire. The results of the partial test obtained are,brand image not impact on consumer satisfaction. Based on the simultaneous test of variables brad image (x1) and price (X2) simultaneously impact on consumer satisfaction (y).